Korporatism och bostadsregimer (Sociologisk Forskning, 2003)
Housing has been described as “the wobbly pillar under the welfare state”. Unlike the other three pillars - education, health and social security - housing is largely a market commodity modified by subsidies and regulation. This makes it a potentially fruitful welfare sector to examine the interplay between market interests and policymaking. This article considers the relationship between rental housing and the welfare state interms of regime theory. Rental housing systems are divided into two types: dualist (profit rental market and residual public poor housing sector) and unitary (not-for-profit integrated into the market). Taking Esping-Andersens Three Worlds of Welfare thesis as a starting point, no Nordic social democratic regime type can be identified for housing, but in relation to classic corporatist theory, unitary rental markets are clearly associated with corporatist societies. The discussion concludes with a consideration of sector regimes in general and housing regimes in particular. It is concluded that theories of power should be more widely applied to housing, and that housing can provide an invaluable empirical laboratory for refining our understanding of both sector regimes and welfare regimes.